3x^2 + 19x - 14=0

For an equation ax^2 + bx +c=0

Quadratic formula for solving for x:

X= (-b ± (b^2 - 4*a*c)^(1/2))/2a

here , a = 3, b = 19 , c = -14

x= (-b ± (b^2 - 4*a*c)^(1/2))/2a

x = [ (-19 ± [ (-19)^2- 4x3x-14) ^ 1/2 ] / 6

x = -19 ± ( 361 + 168 ) ^ 1/2 / 6

x = -19 ± 23 / 6

x = 2/3 or x = - 7

For an equation ax^2 + bx +c=0

Quadratic formula for solving for x:

X= (-b ± (b^2 - 4*a*c)^(1/2))/2a

here , a = 3, b = 19 , c = -14

x= (-b ± (b^2 - 4*a*c)^(1/2))/2a

x = [ (-19 ± [ (-19)^2- 4x3x-14) ^ 1/2 ] / 6

x = -19 ± ( 361 + 168 ) ^ 1/2 / 6

x = -19 ± 23 / 6

x = 2/3 or x = - 7